Tropical Vegetable Diseases: I - Shouan Zhang; Geoffrey Meru; Ken Pernezny; Mary Lamberts (EDIS)
This fact sheet describes the symptoms of several diseases commonly observed on Florida tropical vegetables and provides recommendations for control. This version updated with new author Geoffrey Meru.